2009
DOI: 10.1007/s00330-009-1408-4
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of the posterior hypophysis in children with tuberculous meningitis

Abstract: The syndrome of inappropriate antidiuretic hormone secretion (SIADH) contributes to the morbidity and mortality in children with tuberculous meningitis (TBM). MRI assists in the early diagnosis of TBM and absence of the normal posterior pituitary bright spot (PPS) on T1-weighted MRI in TBM may indicate the functional integrity of the posterior hypophysis. The objective of this retrospective descriptive study of 22 children with TBM was to determine the prevalence of an absent PPS on T1-weighted MRI in children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The inflammatory response and granulation tissue formation in CNS TB is commonly concentrated around the basal cisterns [16]. CNS TB associated endarteritis and vascular thrombosis could result in destruction of parts of pituitary gland and disruption of the hypothalamichypophysial pathways which lie in close anatomical proximity [12]. As a result of these, there could be a decreased storage of vasopressin in posterior pituitary thereby causing absence of PPBS.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The inflammatory response and granulation tissue formation in CNS TB is commonly concentrated around the basal cisterns [16]. CNS TB associated endarteritis and vascular thrombosis could result in destruction of parts of pituitary gland and disruption of the hypothalamichypophysial pathways which lie in close anatomical proximity [12]. As a result of these, there could be a decreased storage of vasopressin in posterior pituitary thereby causing absence of PPBS.…”
Section: Plos Onementioning
confidence: 99%
“…The loss of normal posterior pituitary bright spot (PPBS) was previously described in primary diabetes insipidus and in water intoxication [10,11]. Andronikou et al had found that there was absence of PPBS in 55% of children with TB meningitis [12]. However, its absence in adults with CNS tuberculosis hasn't been studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…MRI has been demonstrated to be superior to CT in diagnosing TBM and its associated complications. [28][29][30] In particular, it is more sensitive in detecting basal enhancement, tuberculomas, and infarcts for diagnosis and prognosis in pediatric TBM. It is, however, unlikely to make an impact on the worldwide diagnosis of TBM because of the limited access to MRI in areas where TBM occurs more frequently.…”
Section: Ademmentioning
confidence: 99%
“…MRI has been demonstrated to be superior to CT in diagnosing TBM and its associated complications 28–30 . In particular, it is more sensitive in detecting basal enhancement, tuberculomas, and infarcts for diagnosis and prognosis in pediatric TBM.…”
Section: Specific Issues When Diagnosing Cns Tb and The Role Of Mrimentioning
confidence: 99%
“…Inflammation and granulation tissue is most prominent in the suprasellar cistern, surrounding the pituitary gland and hypothalamus. It is thought that this inflammation may be the cause of the syndrome of inappropriate anti-diuretic hormone secretion/diabetes insipidus that is seen in up to 70% of children [ 66 ]. Meningeal, parenchymal and ependymal tuberculoma formation can be seen in 15% of children with TB meningitis.…”
Section: Introductionmentioning
confidence: 99%